Is Weight-Bearing Asymmetry Associated with Postural Instability after Stroke? A Systematic Review - Jip F. Kamphuis; Digna de Kam; Alexander C. H. Geurts; Vivian Weerdesteyn (Stroke Research and Treatment)
Introduction. Improvement of postural stability is an important goal during poststroke rehabilitation. Since weight-bearing asymmetry (WBA) towards the nonparetic leg is common, training of weight-bearing symmetry has been a major focus in post-stroke balance rehabilitation. It is assumed that restoration of a more symmetrical weight distribution is associated with improved postural stability. Objective. To determine to what extent WBA is associated with postural instability in people after stroke. Methods. Electronic databases were searched (Cochrane, MEDLINE, EMBASE, and CINAHL) until March 2012. Main Eligibility Criteria. (1) Participants were people after stroke. (2) The association between WBA and postural stability was reported. Quality of reporting was assessed with the STROBE checklist and a related tool for reporting of confounding. Results. Nine observational studies met all criteria. Greater spontaneous WBA was associated with higher center of pressure (COP) velocity and with poorer synchronization of COP trajectories between the legs (two and one studies, resp.). Evidence for associations between WBA and performance on clinical balance tests or falls was weak. Conclusion. Greater WBA after stroke was associated with increased postural sway, but the current literature does not provide evidence for a causal relationship. Further studies should investigate whether reducing WBA would improve postural stability.